Computational Elastic Analysis of AA7075-O using 3D-Microstructrure-Based-RVE with Really-distributed Particles. (1st May 2022) - Sun, Qingping; Jain, Mukesh K.
Highlights: Presents a novel computationally-efficient reconstruction of 3D Representative Volume Element (RVE) model of second-phase particle-strengthened AA7075-O sheet with real distribution of particles based on FIB-SEM techniques Three types of second-phase particles (i.e., irregularly-shaped iron-rich particle Al3 Fe, elliptically-shaped particle MgZn2, and needle-like particle CuAl2 ) are determined using SEM-based EDS and EBSD techniques Presents a systematic study of the overall elastic response by using 3D-microstructrure based RVE Model with periodic boundary condition (PBC) and kinematically uniform boundary condition (KUBC) A comparison of RVE results with that of modified rule of mixtures (MROMs) is presented. MROMs predictions of elastic properties generally well match with the trends of RVE-based computational results, which implies the validity of simpler MROMs approach Abstract: AA7075 is of special interest amongst aluminum alloys for structural applications in automotive and aerospace industries because of its higher strength. Due to advances in experimental and numerical analysis tools, there is much interest amongst researchers in developing analytical and computational methods to calculate the effective material properties of AA7075 alloy based of its complex microstructure. This paper presents a novel computationally-efficient reconstruction of three-dimensional microstructure of representative volume element model with real distribution of particles using focused ion beam equipped with scanning electron microscopy techniques and specialized computer software to investigate the mechanical properties of AA7075-O sheet. As part of material microstructure characterization for computational analysis, particle identification and chemical characterization of the AA7075-O sheet are also investigated by scanning electron microscopy-based energy dispersive X-ray spectroscopy and electron back-scatter diffraction analysis. The results show that there are three main types of particles that exist in AA7075-O sheet, i.e., irregularly-shaped iron-rich particle Al3 Fe, elliptically-shaped particle MgZn2, and needle-like particle CuAl2 . The spatial distribution of these particles in AA7075-O sheet from a set of scanning electron microscopy images are utilized to reconstruct RVE models in a finite element analysis environment and analyzed with periodic boundary condition and kinematically uniform boundary condition. Also, a comparison of RVE results with that of modified rule of mixtures is presented. It is shown that the particular boundary conditions have almost no influence over the effective elastic properties when the RVE size is 10 um × 10 um × 10 um and volume fraction of particle is large. Also, the modified rule of mixtures predictions of elastic properties generally well match with the trends of RVE-based computational results, which implies the validity of simpler modified rule of mixtures approach. Graphical abstract: Image, graphical abstract